What is New in Pediatric Orthopaedic Foot and Ankle. Issue 5 (10th May 2022) - Tileston, Kali; Baskar, Danika; Frick, Steven L.
Abstract : Background: This paper aims to report on the last 5 years of relevant research on pediatric foot and ankle pathology with specific focus on clubfoot, congenital vertical talus, toe walking, tarsal coalitions, pes planovalgus with or without accessory navicular, foot and ankle trauma, and talar dome osteochondritis dessicans. Methods: The Browzine platform was used to review the table of contents for all papers published in the following target journals related to the treatment of pediatric foot and ankle conditions. Search results were further refined to include clinical trials and randomized controlled trials published from March 1, 2015 to November 15, 2021. Results: A total of 73 papers were selected for review based on new findings and significant contributions in treatment of clubfoot, congenital vertical talus, toe walking, tarsal coalitions, pes planovalgus with or without accessory navicular, foot and ankle trauma, and talar dome osteochondritis dessicans. Also included were several papers that did not fit into any of these categories but provided new insight into specific foot and ankle pathologies. Conclusions: Treatment strategies for children with foot and ankle pathology are continually evolving. We review many of the most recent publications with the goal of improving understanding of these pathologies and highlighting current best practices. Level of Evidence: Level III.